2022
DOI: 10.3390/agronomy12061361
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Biostimulants Differentially Modulate Primary and Secondary Metabolites and Improve the Yield Potential of Red and Green Lettuce Cultivars

Abstract: The use of biostimulants in modern agriculture has rapidly expanded in recent years, owing to their beneficial effects on crop yield and product quality, which have come under the scope of intensive research. Accordingly, in the present study we appraised the efficacy of two plant-derived biostimulants, the legume-derived protein hydrolysates Trainer®® (PH), and the tropical plant extract Auxym®® (TPE) on two lettuce cultivars (green and red salanova®®) in terms of morpho-physiological and biochemical traits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Their function, among others, is to donate electrons to peroxidases for H 2 O 2 detoxification, thus acting like antioxidants, and are involved in the mechanical strengthening tissues to enhance the resistance to water deficit [ 33 ]. When looking at the phenolic acid assays, both Trainer and Vegamin biostimulants increased chlorogenic acid, which is the most present phenolic acid in lettuce, in accordance with previous studies in the literature, which found similar increases [ 34 , 35 ]. However, when the leaf flavonoids are considered, we found quercetin-3-glucoside or cyanidin 3-glucoside, and anthocyanin [ 36 ] contents to be increased in both control and salt conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Their function, among others, is to donate electrons to peroxidases for H 2 O 2 detoxification, thus acting like antioxidants, and are involved in the mechanical strengthening tissues to enhance the resistance to water deficit [ 33 ]. When looking at the phenolic acid assays, both Trainer and Vegamin biostimulants increased chlorogenic acid, which is the most present phenolic acid in lettuce, in accordance with previous studies in the literature, which found similar increases [ 34 , 35 ]. However, when the leaf flavonoids are considered, we found quercetin-3-glucoside or cyanidin 3-glucoside, and anthocyanin [ 36 ] contents to be increased in both control and salt conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Main flavonoids in our samples were luteolin-7-glucoside and various quercetin derivates ( Table 2 ). Green and red Salanova lettuce exhibited a higher content of luteolin-7-glucoside, quercetin-3-glucoside, and quercetin-3′-O-glucuronide than the same variety in the research of Giordano et al [ 47 ]. Even though, results of some previous research for the quercetin derivates are in accordance with our samples [ 6 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results were calculated as the logarithm base 1.2 (Log 1.2 ) ratio of biostimulant treatments to control plants. Results were visualized using a false color scale with red indicating an increase and blue a decrease, whereas white squares indicated no differences [ 82 ].…”
Section: Methodsmentioning
confidence: 99%